Pengaruh Product Assortment, In-Store Display, dan Price Perception terhadap Perilaku Pembelian Impulsif Konsumen Iwaka Supermarket - Putu Clara Aldama Fridayanti; Ketut Elly Sutrisni (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to determine the effect of product assortment, in-store display, price perception partially and simultaneously on consumer impulsive purchases. The sample in this study was 70 Iwaka Supermarket consumers. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, it was found that product assortment had a positive and significant effect on consumer impulsive purchases, in-store display had a positive and significant effect on consumer impulsive purchases and price perception had a positive and significant effect on consumer impulsive purchases. Suggestions that can be given by researchers are that Iwaka Supermarket should increase the variety of product sizes, so that later products with various size variations are available, rearrange shelves that have not looked attractive and provide discounts in large purchases on some products that have higher prices than competitors and build a comfortable store atmosphere, so that later it can create a feeling of pleasure when consumers shop.